Initial characterization of an outbreed mouse model for male factor (in)fertility. (11th July 2013) - Michaelis, M.; Langhammer, M.; Hoeflich, A.; Reinsch, N.; Schoen, J.; Weitzel, J. M.
Summary: We analysed an outbreed mouse line which was selected for the phenotype 'high fertility' for 158 generations. During this selection period the mouse strain increased the number of offspring per litter from 10.4 to 17.1 and the total litter weight up to ~160%. In this study, we initially characterize the reproductive phenotype of high fertility males. Surprisingly, male bucks of the fertility line (FL1) show reduced percentage of motile and progressive motile spermatozoa; however, other sperm motility characteristics (e.g. velocity parameters) are improved compared with an unselected control line. Cytometrical investigation of the testicular cell‐type composition indicated a significant increased concentration of diploid cells by a concomitant reduction in haploid cells in the testicular parenchyma of FL1. Furthermore, total testosterone concentrations in blood are dramatically increased in FL1 (>20 ng/mL). In line with increased testosterone levels, we observed increased expression rates of steroidogenic key enzymes Cyp11 and Cyp17 from FL1 testis samples. These data indicate that FL1 males have a manifest 'high fertility phenotype'. Diallelic crosses imply that male‐only contribution largely determines the reproductive outcome in cross‐breeding experiments. FL1 therefore is a promising model for future investigations on male factor (in)fertility. Our observation might also offer valuable cues for human reproductive medicine.